Asociación entre las diferentes entidades clínicas, el leucograma y la presencia de bandas neutrófilas en pacientes hospitalizados en la Clínica León XIII, Medellín, Colombia (2016)
ABSTRACT: The presence of neutrophil bands in peripheral blood is widely used in clinical settings to support the diagnosis of patients with a suspected bacterial infection. However, the diagnostic accuracy of these cells’ relative counts, which is necessary for the diagnosis of bacterial infection, is limited due to low sensitivity. Methods: a total of 242 hemograms of hospitalized patients in the León XIII Clinic were included. These patients presented left-sided alarms in the ADVIA® 2120/2120i hematology equipment and increased neutrophil bands greater than 5% in the peripheral blood smear. Data about age, sex, microbiological results and levels of C-reactive protein of the patients was also gathered. The statistical analysis was performed in SPSS software, together with a Spearman correlation analysis and a Kruskal-Wallis H test. Results: a high variability was observed in the relative count of the neutrophil bands in the different clinical entities. Nonetheless, a significant increase of these cells was found in other non-infectious diseases such as renal and pulmonary diseases with a median of 25 and 22.5 respectively, above bacterial infections with a median of 19 cells. Conclusions: the increase of the neutrophil bands was not related to any particular pathology, which is why its diagnostic value has little use to be correlated with a bacterial infection exclusively.